1975
DOI: 10.1111/1523-1747.ep12610200
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Regeneration Of The Dermal-Epidermal Junction After Partial Separation By Vacuum: An Electron Microscopic Study

Abstract: A process of rapid repair of dermal-epidermal adherence, as found in experiments with interrupted suction, was investigated electron microscopically. Biopsies in different stages of the process of suction blister formation and of the repair process were studied. Results show that suction blister formation occurs by successive detachment of hemidesmosomes from the basement membrane, and that, after partial separation of the epidermis from the dermis, a rapid regeneration of the dermal-epidermal junction takes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

1978
1978
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 20 publications
0
18
0
1
Order By: Relevance
“…In previous studies, however, it was reported that not basal keratinocytes but suprabasal keratinocytes appeared to move by rolling or sliding over the basal layer below (Beerens et al 1975;Gibbins 1978;Krawczyk 1971;Sciubba 1977;Winter 1972). Such a conclusion was also made by Ortonne et al (1981) based on an observation that migrating keratinocytes were stained with KL1 antikeratin antibody against the 67- Fig.…”
Section: Discussionmentioning
confidence: 95%
“…In previous studies, however, it was reported that not basal keratinocytes but suprabasal keratinocytes appeared to move by rolling or sliding over the basal layer below (Beerens et al 1975;Gibbins 1978;Krawczyk 1971;Sciubba 1977;Winter 1972). Such a conclusion was also made by Ortonne et al (1981) based on an observation that migrating keratinocytes were stained with KL1 antikeratin antibody against the 67- Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Cantharidin exposure results in intraepidermal blistering due to degradation of the dense desmosomal plaque within the epidermis [30] . Suction blisters are formed due to detachment of hemidesmosomes from the basement membrane at the epidermal junction [31] . In a brief review of articles involving both blister types, there was insufficient data to justify the pooling of data on the two blister types.…”
Section: Discussionmentioning
confidence: 99%
“…Soon, the necrotic epidermis forming the blister is sloughed off, leaving behind an epidermis-free surface. Keratinocytes migrate from the injured edges and reattach themselves onto the inner layer (lamina densa) of the relatively intact basement membrane (Krawczyk and Wilgram 1973;Beerens et al 1975). Keratinocyte migration also originates in the appendages of skin (hair follicles, sweat glands, sebaceous glands) that are located in the dermis.…”
Section: The Epidermocentric Viewpoint In Studies Of Skin Wound Healingmentioning
confidence: 99%